2007
DOI: 10.1152/ajpregu.00352.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on the cardiovascular regulatory systems in healthy women

Abstract: Aging, independently from the hormonal status, is a major risk factor for cardiovascular morbidity in healthy women. Therefore, we studied the effect of healthy aging on the cardiovascular homeostatic mechanisms in premenopausal and postmenopausal women with similar estrogen levels. Twelve healthy postmenopausal women, confirmed by follicular-stimulating hormone (FSH) and luteal hormone (LH) levels, were compared with 14 normally menstruating women during the early follicular phase (young-EF), to avoid as much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
66
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 46 publications
2
66
0
1
Order By: Relevance
“…A greater percentage of lowthreshold Ah-type myelinated afferents may account for the predominant vagal tone in females compared with agematched males (8). A recent study by Lavi et al (28) has documented that numerous indexes of vagal cardiac tone in postmenopausal women were significantly decreased from those of premenopausal women. There is growing support in the literature for the suggestion that a transition from vagal parasympathetic to sympathetic control of neurocirculation may contribute to the increased cardiovascular morbidity of females with aging (28).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A greater percentage of lowthreshold Ah-type myelinated afferents may account for the predominant vagal tone in females compared with agematched males (8). A recent study by Lavi et al (28) has documented that numerous indexes of vagal cardiac tone in postmenopausal women were significantly decreased from those of premenopausal women. There is growing support in the literature for the suggestion that a transition from vagal parasympathetic to sympathetic control of neurocirculation may contribute to the increased cardiovascular morbidity of females with aging (28).…”
Section: Discussionmentioning
confidence: 98%
“…A recent study by Lavi et al (28) has documented that numerous indexes of vagal cardiac tone in postmenopausal women were significantly decreased from those of premenopausal women. There is growing support in the literature for the suggestion that a transition from vagal parasympathetic to sympathetic control of neurocirculation may contribute to the increased cardiovascular morbidity of females with aging (28). OVX female rats have been shown to exhibit enhanced sympathetic activation and attenuated vagal tone, and it has been shown that acute injection of 17␤-estradiol can enhance vagally mediated cardiovascular reflexes and autonomic tone (11,44).…”
Section: Discussionmentioning
confidence: 98%
“…Investigations of men and women from 23-77 yr of age indicated that the heart rate response to tilt was reduced with aging, but vascular responses appeared to be enhanced to protect against low blood pressure (17,32). A study that focused on postmenopausal women also reported a reduction in arterial baroreflex responsiveness and heart rate control characterized by greater sympathetic and reduced parasympathetic modulation (33). Another investigation revealed that, during lower body negative pressure (LBNP), postmenopausal women had higher systolic (SBP) and mean arterial blood pressures (MAP) with an attenuated increase in heart rate compared with premenopausal women (21).…”
mentioning
confidence: 99%
“…For example, aging of healthy women is associated with a decrease in the parasympathetic modulation of the heart in the setting of a preserved sympathetic tone leading to a net predominance of sympathetic control. 2 Decreased baroreflex buffering ability is also seen with advancing age. 2 Moreover, imaging studies after adjustment for perfusion changes in healthy hearts have shown that cardiac uptake 1 activity decreases with aging.…”
mentioning
confidence: 99%
“…2 Decreased baroreflex buffering ability is also seen with advancing age. 2 Moreover, imaging studies after adjustment for perfusion changes in healthy hearts have shown that cardiac uptake 1 activity decreases with aging. 3 These observations corroborate well with the known evidence on the increased cardiac norepinephrine spillover during normal aging 4 and potentially make older hearts appear pre-disposed to catecholamine exposure in a given stressful situation.…”
mentioning
confidence: 99%